Bio-sensitizing learning societies: A culture servicing to the environment at the Liberia- Sede Regional Chorotega Campus, Costa Rica - Castro Castillo, Wagner (2014)
The university must propose strategic actions in pursuit of knowledge, conservation, and the management of biodiversity free of destructive practices. A new type of education is necessary, where science, art and spirituality are complementary and are aimed at the development of a whole human being, one who is able to be more human. This is important for the development of global and comprehensive education in the world of this new millennium. Teachers must strengthen the educational process as an alternative academic proposal, based on bio-pedagogy, for the reflection, production, and exchange through ecologicallycentered values that will ensure joy, love, understanding and care to contribute to our imagination. Nature, the human being, and society are interdependency, symbiosis, they are connected by the umbilical cord which for centuries has kept it linked to the universe.